2008
DOI: 10.1002/ca.20737
|View full text |Cite
|
Sign up to set email alerts
|

Do the vastus medialis obliquus and vastus medialis longus really exist? A systematic review

Abstract: There remains controversy over whether the vastus medialis (VM) is a single anatomical structure or whether it is composed of two separate portions, the vastus medialis longus (VML) proximally and the vastus medialis obliquus (VMO) distally. The objective of this study was to assess the evidence base of investigations into muscle fiber orientation, presence of a fibrofascial plane, and the innervation of the VM in human cadaver specimens and subjects. In addition to a hand search of specialist journals, an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 56 publications
4
34
1
1
Order By: Relevance
“…There is no consensus in the literature as to whether these two components are separate muscles, or whether they reflect different directional fibers of the same muscle. 2,3 On MR imaging, the normal appearance of the trilaminar quadriceps tendon manifests as low-signal tendon fibers with interdigitating fat (Fig. 1).…”
Section: Normal Anatomymentioning
confidence: 99%
“…There is no consensus in the literature as to whether these two components are separate muscles, or whether they reflect different directional fibers of the same muscle. 2,3 On MR imaging, the normal appearance of the trilaminar quadriceps tendon manifests as low-signal tendon fibers with interdigitating fat (Fig. 1).…”
Section: Normal Anatomymentioning
confidence: 99%
“…An example is vastus medialis, where substantial alterations in fibre alignment are seen between proximal and distal muscle portions (Smith et al , 2009). The distal oblique fibres are thought to play a pivotal role in the kinematics and alignment at the patellofemoral joint (Berry et al , 2008, Fagan and Delahunt, 2008, Lin et al , 2008 and physiological or biomechanical dysfunction of this muscle are reported to contribute to patellofemoral pain (PFP) (Lankhorst et al , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biceps brachii is easy to measure and very rarely used in tensiomyography studies. Furthermore, there is evidence that the vastus medialis is anatomically divided into two muscle heads (obliques and longus) with two separate neural drives (Smith et al, 2009) and should be measured accordingly. In most tensiomyographic studies, the vastus lateralis and biceps femoris muscles have been investigated (Dahmane et al, 2006;Ditroilo et al, 2011;García-Manso et al, 2011a,b;Grabljevec and Tomšič, 2002;Pišot et al, 2008;Rusu et al, 2009;Šimunič et al, 2011); however, no tensiomyographic measurement reliability is reported for those two muscles.…”
Section: Introductionmentioning
confidence: 99%